Teaching Strategy of Al-Islam Teacher on Increasing Student’s Morality in 9 Grade of SMP Muhamadiyah 15 Surabaya - Ahmad Fathullah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
This study aimed to determine the role of teacher to student's morality education, the strategy of Al - Islam teacher to improve student morality, the supporting factors and inhibitors in building student's morality of 9 grade student in SMP Muhammadiyah 15 Surabaya. This study used descriptive qualitative method. The research data were collected by using observation, interview and documentation method, then analyzed by using inductive approach and validity test. The results indicated that: activities of moral formation that teachers do i.e. night prayer, tahfidz Qur'an, and dzuhur praying in congregation. Teaching strategies of PAI Teacher used inquiry strategies, approached to student by using a variety of methods such as lecturing method, habituation method, and counseling method. The supporting factors: (a) family factors or parent who has very active role to participate in fostering student's morality, (b) environment or community around the school, (c) the environment around student's residence has been thick with religious thing, (d) school’s rules to prevent student's delinquency. Inhibiting Factors are (a) there was no enough time to foster much morality on student. (b) Lack of school's provision. (c) Different student's attitude and behavior. (d) Uncontrollable student association. (e) Lack of students’ awareness to attend activities required by the school. (f) Inadequate supporting facilities and infrastructures. (g) The widespread of information today. Keywords: Role, Strategy, Moral Education